Patient-Centered Dentinal Hypersensitivity Treatment Outcomes: Results from the National Dental PBRN. (January 2018) - Heft, M.W.; Litaker, M.S.; Kopycka-Kedzierawski, D.T.; Meyerowitz, C.; Chonowski, S.; Yardic, R.L.; Gordan, V.V.; Mungia, R.; Gilbert, G.H.; ,
Dentinal hypersensitivity (DH) can have a significant impact on oral health and functioning, and it is a clinical symptom commonly managed by dentists during routine clinical practice. DH symptoms are typically elicited by otherwise innocuous, nonpainful stimuli applied to exposed dentin (e.g., tactile stimuli, warming or cooling temperatures or air puffs). Treatment approaches have sought to directly target the dentinal pulp tissues or close dentinal tubules via dental office care and treatment services (fluoride varnishes, glutaraldehydes, bonding agents, sealants, oxalates, or lasers) or home care services (toothpastes or dentifrices containing fluoride or potassium nitrate compounds). The purpose of this prospective multicenter cohort study was to assess how community-based dentists from the National Dental Practice-Based Research Network (National Dental PBRN) manage DH and whether the effectiveness of DH treatments can be assessed in those settings. A total of 171 dentists recruited 1862 subjects with DH from their existing patients. Dentists then recommended and provided DH treatment as appropriate. Treatment choice was at the discretion of the dentists. Patients rated their DH pain at baseline and 1, 4, and 8 wk during the course of their treatments. They used pain intensity and unpleasantness visual analog scales and 4 labeled magnitude scales and rated their satisfaction with treatment after 8 wk. Patients were provided reminders postbaseline via email, texting, or voice mail. These patient-centered outcomes served as the principal measures for the assessment of treatment because treatments sought to alleviate DH symptoms. The patients with DH who reported pain reduction from dentist-provided treatments (glutaraldehyde/HEMA [hydroxyethyl methacrylate] compounds, oxalates, and bonding agents), dentists' advice and counseling regarding oral habits and diet, and patient-applied fluoride toothpaste reported a concomitant positive rating of satisfaction with DH treatments. The results from this study support the feasibility of engaging network practices to assess the effectiveness of clinical DH treatments. Knowledge Transfer Statement: National Dental PBRN dentists provide a range of procedures to treat dentinal hypersensitivity. In this large nonrandomized study designed to assess clinical care and to capture patient-reported outcomes, about 60% of patients reported improvement in pain. This study demonstrated the feasibility of engaging network dentists and their patients to assess treatment effectiveness. Future studies will explore the feasibility of imposing randomization and measuring patient compliance with treatment in the manner that this treatment is provided.